Prayers for Ukraine and Peace in the “Times of Tribulation and Division” - Naumow, Aleksander (Poznańskie Studia Slawistyczne, 2016)
Based upon web-published materials, the article analyzes the eulogies composed in the Church Slavonic and Ukrainian languages, which have arisen following Kiev’s Maidan and its subsequent developments in the period December 2013 – December 2014. The texts under analysis come from Ukrainian Orthodox Church of the Moscow Patriarchate and from the Patriarchate of Moscow itself, from the Ukrainian Orthodox Church of the Kiev Patriarchate and some other texts. Initiatives from the laity are also taken in account (e.g. Ruslana Lyžyčko). The prayers under analysis show historical and political influences. In the Muscovite texts and in Patriarch Kirill’s statements, the attempt to impose the idea of a Russian Commonwealth (Russkij mir) is quite evident. This idea is based upon the unity and brotherhood of a people united by the christening of the Prince St. Vladimir. There are also charges brought against Greek Catholics and non-canonical Churches. The texts composed in Ukraine are either more decisively patriotic and anti-muscovite, with statements backing the European project (the Kiev Patriarchate Ukrainian Orthodox Church), or more religious in general terms, with a plea for fundamental Christian values and declarations of loyalty towards the State (the Moscow Patriarchate Ukrainian Orthodox Church).